Case Report: Novel Arylsulfatase A (ARSA) Gene Mutations in a Patient With Adult-Onset Metachromatic Leukodystrophy Misdiagnosed as Multiple Sclerosis - Xu, Lulu; Zhong, Meixiang; Wang, Yajuan; Wang, Zhihong; Song, Jie; Zhao, Jing; Yu, Hongyun; Yang, Zhencui; Yan, Wenjing; Zheng, Xueping (Frontiers in Neurology, 2021)
Metachromatic leukodystrophy (MLD) is an autosomal recessive hereditary disorder characterized by the accumulation of sulphatide in the central and peripheral nervous system. Here, we present an adult MLD patient with mild cognitive and psychiatric dysfunctions and severe vision disturbance initially misdiagnosed as multiple sclerosis. This patient was later diagnosed with a large fragment deletion of exon 4 and the novel p.P220L mutation in the ARSA gene through gene screening. These mutations are reported for the first time in MLD patients. The data will help in updating the mutation profiles.